The influence of a modified ball on transfer of passing skill in soccer. (November 2018) - Oppici, Luca; Panchuk, Derek; Serpiello, Fabio Rubens; Farrow, Damian
Abstract: Objectives: Equipment is frequently modified to promote skill learning in sport. However, it is unclear whether skills learned using modified equipment transfer to the criterion task. This study examined the transfer of passing skill from practicing with a futsal ball to performing with a soccer ball, and the perceptual skill underlying the process. Methods: 24 adult novices (n = 18 females and n = 6 males, 24 ± 4.8 years old) were divided into an experimental (FUT) and a control group (SOC). The two groups practiced the same passing skill in response to video stimuli across 3 sessions, the FUT group used a futsal ball and SOC group used a soccer ball. Passing performance and gaze behaviour were assessed pre- and post-intervention using a soccer ball in both groups to evaluate transfer. Results: FUT showed greater pre- to post-test improvement (Effect Size (ES) = 2.06 ± 0.86) in passing performance than SOC (ES = 1.03 ± 0.82), and higher passing performance in a time-constrained scenario in the post-test (ES = 1.83 ± 1.07). The higher passing performance in FUT was underpinned by changes in gaze behaviour. FUT increased the number of fixation alternations between the ball and other locations and changed the cues learners focused their attention on, while SOC only slightly modified their gaze behaviour. Conclusions: This study showed that modified equipment – futsal ball – shaped the development of a behavioural repertoire that positively transferred to other equipment – soccer ball – improving learning of a perceptual-motor skill. Practitioners working in soccer are encouraged to use a futsal ball in their training sessions to fast-track learning, particularly in novices. Highlights: A modified ball - futsal ball - promoted transfer of passing skill to a standard ball. Practicing passes with the modified ball encouraged changes in participants' gaze behaviour. The changes in gaze behaviour underpinned positive transfer of the passing skill. Practitioners working in soccer are encouraged to use this modified ball to promote their athletes' skill development.